Data acquisition and processing system for local seismologic networks - Guada Barráez, Carlos; Silva Trujillo, José (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
An automatic seismic data acquisition and processing system has been designed and implemented in the Los Andes University Geophysical Laboratory. It has been tailored to meet the needs of the seismological observatories interested in gathering, structuring and publishing on the Internet the necessary data to carry out microseismicity studies. The system was designed to facilitate its operation and maintenance at a relatively low cost. This goal was achieved by exploiting the capabilities of the networks based on personal computers and on the family of the Microsoft Windows operating system. Real time data acquisition is performed using an A/D card and a driver, both of which were specially designed to detect seismic events. The time baseline of the seismic records is automatically synchronized with the time signal from a satellite clock, obtaining the millisecond accuracy necessary for precise timing of the seismic signals. The seismic detection algorithm work through both, the time and frequency domain, using neural networks for the recognizance of seismic wave patterns. Triggering of several seismic stations is used as an additional discrimination criterion. Off-line seismic data processing can be performed on any PC connected to the local network or TCP/IP. The processing includes seismogram visualization, arrival times and polarities picking, hypocenter locations, plotting epicenter maps and access to seismic libraries. Moreover, capabilities for dynamic publication in web sites is provided via an interactive catalog, which also allows seismologists to locate through the WWW the information needed for their research. The software is interactive and integrated and, following a set of rules, it can be extended with new functions. All information, either from individual events or from groups of events, including their seismograms, can be displayed using an information base, which can be managed through the Internet. Most of the versatility of this information base is due to its capability to store and relate instrumental data from seismic events with digital documents, allowing several ways of searching and collection information. This work allowed the automation of the Venezuelan Andes Seismic Network operated by the Los Andes University Geophysical Laboratory (http://lgula.ciens.ula.ve) at the beginning of the nineties. Its algorithm for event discrimination, and capabilities for integrated management of the information and low cost operational maintenance, have been tested in seismic networks in southern Venezuela for almost a decade, being accumulated the biggest seismological information base available about South West of Venezuela.